2022
DOI: 10.31223/x5kp8m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global fast-traveling tsunamis by atmospheric pressure waves on the 2022 Tonga eruption

Abstract: Please note this manuscript is a non-peer reviewed EarthArXiv preprint and has not formally been accepted for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The rst atmospheric disturbance R1 is expected to be Lamb waves, an acoustic mode of air waves with a propagation velocity of approximately 300 m/s (Lamb 1932;Nishida et al 2014). Kubota et al (2022) clari ed through a global simulation that the atmospheric pressure disturbance of Lamb waves generated by the 2022 Tonga eruption forcibly induced the uplift of sea-surface and that a superposition of the atmospheric pressure change by the Lamb waves and the induced sea surface change was observed by ocean-bottom pressure gauge as ocean-bottom pressure. This can explain the similar waveform and arrival time in the rst disturbance for atmospheric pressure and ocean-bottom pressure.…”
Section: Distributions Of Peak Amplitude and Peak Timementioning
confidence: 99%
See 3 more Smart Citations
“…The rst atmospheric disturbance R1 is expected to be Lamb waves, an acoustic mode of air waves with a propagation velocity of approximately 300 m/s (Lamb 1932;Nishida et al 2014). Kubota et al (2022) clari ed through a global simulation that the atmospheric pressure disturbance of Lamb waves generated by the 2022 Tonga eruption forcibly induced the uplift of sea-surface and that a superposition of the atmospheric pressure change by the Lamb waves and the induced sea surface change was observed by ocean-bottom pressure gauge as ocean-bottom pressure. This can explain the similar waveform and arrival time in the rst disturbance for atmospheric pressure and ocean-bottom pressure.…”
Section: Distributions Of Peak Amplitude and Peak Timementioning
confidence: 99%
“…5). Kubota et al (2022) suggested that after the arrival of ocean waves due to Lamb waves, ocean gravity waves arrived with theoretically expected tsunami arrival time. These waves originated from various factors such as subsidence ocean waves compensating for uplift by Lamb waves, ocean waves displaced by atmospheric gravity waves and their resonances, and tsunamis directly caused by crustal deformation near the volcano induced by the eruption.…”
Section: Relationship With Atmospheric Pressure Disturbancementioning
confidence: 99%
See 2 more Smart Citations
“…As shown by Kubota et al. (2022), the Hunga Tonga‐Hunga Ha'apai eruption's atmospheric acoustic waves deformed the sea surface so that tsunami‐like water level variations occurred hours before the actual tsunami water wave arrived. Undoubtedly, these acoustic waves also caused ionospheric disturbances.…”
Section: Introductionmentioning
confidence: 99%